International Debt Statistics 2014 - World Bank (Washington, DC, 2014)
International Debt Statistics (IDS) 2014 is a continuation of the World Bank’s publications Global Development Finance, Volume II (1997 through 2009) and the earlier World Debt Tables (1973 through 1996). IDS 2014 provides statistical tables showing the external debt of 128 developing countries that report public and publicly guaranteed external debt to the World Bank’s Debtor Reporting System (DRS). It also includes tables of key debt ratios for individual reporting countries and the composition of external debt stocks and flows for individual reporting countries and regional and income groups along with some graphical presentations.